BENCH TESTS OF THE MODERNIZED TRACTOR DIESEL - V.A. Ovtov; A.A. Orekhov; A.V. Polikanov; Yu.V. Polyvyany (Volga Region Farmland, 2021)
The car and tractor diesel engines are used in various natural and climatic zones of the country, where the ambient temperature varies in a wide range. The effective performance of a diesel engine largely depends on the performance properties of fuel and lubricants exposed to ambient temperatures. The purpose of this work is to study and substantiate the temperature of the fuel in the filling cavity of the high-pressure fuel pump, which ensures the optimal technical and economic performance of the diesel engine. The purpose of the work was achieved by analyzing scientific publications in domestic and foreign peer-reviewed journals, by conducting bench tests of the fuel pump and brake tests of a diesel engine under conditions of a forced change in fuel temperature. Using the method of planning a multifactorial experiment, the optimal temperature range of diesel fuel was determined, which provides the effective performance of a tractor diesel engine. The studies made it possible to determine the optimal technical and economic indicators of a tractor diesel engine.